Analisis Yuridis Terhadap Wabah Corona Sebagai Alasan Force Majaure Dalam Sewa Guna Usaha (Leasing) (Qawanin Jurnal Ilmu Hukum, 2021)
AbstractCurrently the world is shocked by an outbreak of a disease or virus that is verydangerous to humans and is a threat to global health. The name of the virus is Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-COV2) with the name Coronavirus Disease-2019 (COVID-19) or in Indonesia better known as Coronavirus. Coronavirus or corona virus was first discovered in China, to be precise in Hubei province, Wuhan city on December 8, 2019. Then on March 11, 2020 the World Health Organization (WHO) declared COVID-19 a global pandemic after the virus began to spread to 114 countries. .The spread of Covid- 19 initially only exacerbated human health problems, but over time it cannot be denied that Covid-19 has also begun to affect the economic problems of a country. One of them is in the business world, in times like today the continuity of contracts and agreements has experienced some bottlenecks due to the pandemic. The existence of this condition can be used by the debtor as an excuse for renouncing a contract agreement that has been agreed upon with the creditor on the grounds of force or force majeure. Financial institutions engaged in the business world affected by the covid-19 outbreak are ADIRA Finance and BFI Finance. AbstrakSaat ini dunia dihebohkan dengan salah satu wabah penyakit atau virus yang sangat berbahaya bagi manusia dan merupakan ancaman bagi kesehatan global. Nama virus tersebut adalah Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-COV2) dengan nama penyakit Coronavirus Disease-2019 (COVID-19) atau di indonesia lebih dikenal dengan istilah Virus Corona. Coronavirus atau virus korona pertama kali ditemukan di negara China tepatnya di provinsi Hubei, kota Wuhan pada tanggal 8 Desember 2019. Kemudian pada tanggal 11 Maret 2020 World Health Organization (WHO) menetapkan COVID-19 sebagai pandemic global setelah virus tersebut mulai menyebar ke 114 negara. Penyebaran Covid- 19 awalanya hanya memperburuk masalah kesehatan manusia namun lama kelamaan tidak dapat dipungkiri bahwa covid-19 ini juga mulai mempengaruhi masalah perekonomian suatu negara. Salah satunya yaitu dalam dunia bisnis, pada masa seperti sekarang ini kelangsungan kontrak dan perjanjian mengalami beberapa kemacetan akibat pandemi. Adanya kondis ini dapat dijadikan pihak debitur sebagai alasan dalam melakukan pangingkaran suatu kontrak perjanjian yang telah disepekati bersama dengan pihak kreditur dengan alasan memaksa atau force majeure.Lembaga pembiayaan yang bergerak dalam dunia bisnis yang terkena dari adanya wabah covid-19 adalah ADIRA Finance dan BFI Finance.